Audit Quality and Corporate Governance: Evidence from the Microfinance Industry - Leif Atle Beisland; Roy Mersland; R. Øystein Strøm (International Journal of Auditing, 2015)
This study uses a unique hand-collected sample of for-profit and nonprofit microfinance institutions from 70 developing countries to analyse the relationships between audit quality and governance mechanisms. We examine two measures of audit quality, namely, the use of Big Four auditors and the presence of internal auditors. The empirical analysis of this study reveals that these two quality metrics are highly related, although we also demonstrate that these metrics capture distinctive aspects of audit quality. In particular, the presence of internal auditors is related to other indicators of stricter governance, whereas the use of Big Four auditors is generally unrelated to other governance mechanisms. For situations in which a significant relationship between audit quality and governance does exist, the sign of this relationship is always positive. Thus, our data support the complementarity view of these two traits that is espoused by prior research.
Keywords: 650